Effect of immunosuppressants on the parasite load developed in, and immune response to, visceral leishmaniasis: A comparative study in a mouse model. - Lorena Bernardo; Jose Carlos Solana; Alba Romero-Kauss; Carmen Sánchez; Eugenia Carrillo; Javier Moreno (Public Library of Science (PLoS), 2021)
The increasing use of immunosuppressants in areas where visceral leishmaniasis (VL) is endemic has increased the number of people susceptible to developing more severe forms of the disease. Few studies have examined the quality of the immune response in immunosuppressed patients or experimental animals with VL. The present work characterises the parasite load developed in, and immune response to, Leishmania infantum-induced VL in C57BL/6 mice that, prior to and during infection, received immunosuppressant treatment with methylprednisolone (MPDN), anti-tumour necrosis factor (anti-TNF) antibodies, or methotrexate (MTX). The latter two treatments induced a significant reduction in the number of CD4+ T lymphocytes over the infection period. The anti-TNF treatment was also associated with a higher parasite load in the liver and a lower parasite load in the spleen. This, plus a possibly treatment-induced reduction in the number of cytokine-producing Th1 cells in the spleen, indicates the development of more severe VL. Interestingly, the MPDN and (especially) MTX treatments provoked a greater presence of soluble Leishmania antigen-specific multi-cytokine-producing T cells in the spleen and a lower liver parasite load than in control animals. These results highlight the need to better understand how immunosuppressant treatments might influence the severity of VL in human patients.